Evaluation of variation of portal vein branching pattern on Multidetector Computed Tomography in adult population - Adhikari, Kapil; Devkota, Karun; Koirala, Sapana (Nepalese Journal of Radiology, 2021)
Introduction: The main aim of this study was to determine the prevalence of main and right portal vein variation in study population and evaluate their branching patterns on abdominal CT. Methods: A hospital based cross sectional study was carried out in Department of Radiology, BPKIHS over a period of 6 months after taking ethical approval from institutional review committee. 375 cases referred for abdominal CT for various indications were included in the study. Results: Classic main portal vein branching pattern (Type 1) was identified in 305 (81.3%) cases. Main portal vein branching variations were identified in 70 (18.7 %) cases of which most common variation was trifurcation pattern (Type 2) seen in 48 (12.8%) cases followed by right posterior portal vein as first branch of main portal vein (Type 3) seen in 21 (5.6%) cases. Out of 305 cases with Type 1 branching pattern, classic branching pattern of right portal vein was noted in 285 (93.4%) cases. Right portal vein variations were identified in 20 (6.5%) cases. Common variations of right portal vein noted in our study were early origin of segment VlI branch from right portal vein seen in 5 cases (1.6%), early origin of segment VI branch from right portal vein seen in 4 (1.3%) cases and quadrifurcation pattern seen in 3 cases (0.98%). Conclusion: Prevalence of portal vein variations is high on routine abdominal CT scans. Knowledge about branching patterns of these variations can be useful to reduce liver injury and complications during hepatic surgeries and interventions.